Proton pump inhibitors not associated with hypomagnesemia, regardless of dose or concomitant diuretic use. Issue 10 (3rd April 2018) - Chowdhry, Monica; Shah, Kuldeep; Kemper, Suzanne; Zekan, David; Carter, William; McJunkin, Brittain
Abstract: Background and Aim: Proton pump inhibitors (PPIs) are among the most commonly prescribed medications worldwide, with dramatic efficacy for upper gastrointestinal acid‐related disorders. In recent years, however, the safety of long‐term PPI use has been questioned. One issue based on scant and conflicting literature is the possibility of PPI‐related hypomagnesemia. Our purpose was to assess for any clinically significant alteration in serum magnesium levels in large groups of patients taking different PPIs in varying doses, with or without diuretics. Methods: This was a retrospective review of patient records at time of hospitalization, from February 2012 to December 2014. Two thousand four hundred patients were randomly selected from a pool of 12 058 magnesium levels performed at or within 24 h of hospital admission. Patients were categorized in six groups based on outpatient PPI and/or diuretic use. The main outcome studied was hypomagnesemia, defined as serum magnesium level < 1.6 mg/dL. Results: Mean magnesium levels were normal in PPI users (1.84 ± 0.29 mg/dL [normal 1.6 to 2.5 mg/dL]) and PPI nonusers (1.85 ± 0.30 mg/dL), P = 0.40, and there was no statistical difference in the prevalence of hypomagnesemia (14.7% vs 15.1%, P = 0.77). In separate groups, there were also no significant differences in serum magnesium levels between those taking PPIs of varying doses, with or without concomitant diuretics, and those not taking PPIs or diuretics. Conclusion: Regardless of PPI dosage or concomitant diuretics prescribed, magnesium levels were unaffected. Routine screening of serum magnesium in PPI patients appears unnecessary.